Towards a better understanding of Para sport development : A case study of National Paralympic Committee Trinidad and Tobago - Schrieverhoff, Silke (2022)
The Paralympic Games has undergone tremendous growth and developed from means of rehabilitation to the second largest multi-sport event in the world. At its last edition at the Tokyo 2020 Paralympic Games, 162 nations competed in 22 sports. However, when taking a closer look, an inherent imbalance becomes visible. On the one hand, the top six countries alone claim 50 percent of the overall available medals, while on the other hand, almost half of all participating nations competed with a team size of only three or less athletes. But it is not only about medal success at the highest level of competition. The adoption of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) in 2006 manifested access to sport for people with a disability as a human right. To make the Paralympic Movement a truly universal one and ensure that people with a disability have the right to participate in sport in countries around the world, it is essential to understand the underlying challenges in resource-poor countries in advancing Para sport. Using a case study approach, this thesis investigated the operational environment of the National Paralympic Committee Trinidad and Tobago by exploring the external barriers as well as the internal organisational capacities that influence national Para sport development. By assessing the strengths, weaknesses, opportunities, and threats, a greater understanding of the challenges in Para sport development in Trinidad and Tobago was provided. The results highlight that National Paralympic Committee Trinidad and Tobago operates in a challenging environment facing deeply embedded social and environmental barriers as well as the absence of established legal frameworks. Furthermore, internal struggles such as a lack of financial, human, and structural capacity were identified. The study gives a rare insight to the unique characteristics of Para sport development and contributes to the scarce academic field of Para sport in non-Western countries. Future research could apply the same methodology to additional non-Western countries to increase the understanding of Para sport systems and related challenges. Moreover, future research could build on the findings of this study on how to develop the organisational capacity.